THE INFLUENCE OF ORGANIZATIONAL CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE IN SINDANG RERET HOTEL, CIKOLE LEMBANG, WEST BANDUNG REGENCY - Raden Intan Medya Ratna Pury (Media Bina Ilmiah, 2024)
This research is motivated by circumstances where employee performance is not optimal. Not yet optimal organizational culture and motivation are the basis for not optimal performance of hotel and restaurant employees at Sindang Reret Cikole Lembang, West Bandung Regency. The influence of organizational culture and motivation on employee performance at the hotel and restaurant Sindang Reret Cikole Lembang, West Bandung Regency is the aim of this research. Descriptive and verification research are used in this research. Desctiptive survey and explanatory survey are the methods in this determination. Saturated samples were used as the population in this study which were all 106 employees of the hotel and restaurant Sindang Reret Cikole Lembang, West Bandung Regency. Path analysis is used as a method of analysis in this study. The conclusion from this research is that organizational culture has a direct influence on employee performance by 1.18% and a direct influence of motivation on employee performance by 4.96%. Simultaneously, the influence of independent variables on employee performance is 27.2% and other factors influence the remaining 72%.